Clonorchis sinensis-Derived Protein Attenuates Inflammation and New Bone Formation in Ankylosing Spondylitis - Lee, Yu Jeong; Kim, Moon-Ju; Jo, Sungsin; Jin, So-Hee; Park, Pu-Reum; Park, Kijeong; Song, Ho-Chun; Kim, Jahae; Kim, Ji-Young; Shim, Seung Cheol; Kim, Tae-Hwan; Hong, Sung-Jong; et al. (Frontiers in Immunology, 2021)
Helminth infections and their components have been shown to have the potential to modulate and attenuate immune responses. The objective of this study was to evaluate the potential protective effects of Clonorchis sinensis-derived protein (CSp) on ankylosing spondylitis (AS). Cytotoxicity of CSp at different doses was assessed by MTS and flow cytometry before performing experiments. Peripheral blood mononuclear cells (PBMCs) and synovial fluid mononuclear cells (SFMCs) were obtained from AS patients. Inflammatory cytokine-producing cells were analyzed using flow cytometry. The levels of INF-γ, IL-17A, TNF-α, and IL-6 were measured by enzyme-linked immunosorbent assay (ELISA). SKG mice were treated with CSp or vehicles. Inflammation and new bone formation were evaluated using immunohistochemistry, positron emission tomography (PET), and micro-computed tomography (CT). Treatment with CSp resulted in no reduced cell viability of PBMCs or SFMCs until 24 h. In experiments culturing PBMCs and SFMCs, the frequencies of IFN-γ and IL-17A producing cells were significantly reduced after CSp treatment. In the SKG mouse model, CSp treatment significantly suppressed arthritis, enthesitis, and enteritis. Micro-CT analysis of hind paw revealed reduced new bone formation in CSp-treated mice than in vehicle-treated mice. We provide the first evidence demonstrating that CSp can ameliorate clinical signs and cytokine derangements in AS. In addition, such CSp treatment could reduce the new bone formation of AS.